2018
DOI: 10.1111/pirs.12261
|View full text |Cite
|
Sign up to set email alerts
|

Venture capital: The effect of local and global social ties on firm performance

Abstract: Firm financing literature has been dominated by a relatively 'undersocialized' and 'aspatial' view. We approach this gap by applying a social capital and economic geography informed lens to financial transactions. We explore if and how the early growth performance of venture capital backed organizations varies with the structural and physical location of their investors in syndication networks. Drawing on longitudinal data of Belgian firms and their venture capital investors, it is demonstrated that inter-firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…The international network helps firms to be internationally entrepreneurial orientated [54]. As pointed out by Bringmann and Vanoutrive and Verhetsel [55], firms with strong global ties and deep relationship acquire useful resources which configure their innovation competencies and performance while a firm with a lack of ties is often unable to compete effectively in the markets. Therefore, many valuable resources and capabilities can be gained through international network ties and relationship.…”
Section: International Network and Sustainable Competitive Performancementioning
confidence: 99%
“…The international network helps firms to be internationally entrepreneurial orientated [54]. As pointed out by Bringmann and Vanoutrive and Verhetsel [55], firms with strong global ties and deep relationship acquire useful resources which configure their innovation competencies and performance while a firm with a lack of ties is often unable to compete effectively in the markets. Therefore, many valuable resources and capabilities can be gained through international network ties and relationship.…”
Section: International Network and Sustainable Competitive Performancementioning
confidence: 99%
“…Further work by Taylor and Levitt (2005) has focused on knowledge flow, which is an essential part of our study. We have presented valuable content about interorganizational knowledge flows (Baierl et al, 2016;Bringmann et al, 2018;Lee et al, 2017). In the case analysis, we observed that for coopetitors can pool R&D activities and get access to the competitors' resources, as well as knowledge (Bengtsson and Kock, 2000), which can promote innovation (Ritala et al, 2016) and competitiveness.…”
Section: Coopetitive Dynamics and Knowledge Flowsmentioning
confidence: 99%
“…First, the literature suggests that knowledge transfer between VC firms has a positive effect on innovation development in the new ventures (Salvetat et al, 2013;Singh and Stout, 2018;Abrahamsson and Isaksson, 2018). As mentioned in the literature above, VC resources are essential in coopetition and knowledge (Bringmann et al, 2018) as coopetition ensures knowledge transfer as a vital source of competitive advantage in new ventures (Levy et al, 2001;Ilvonen and Vuori, 2013). Accordingly, another knowledge gap emerges regarding the type of relationship between knowledge transfer among VC firms and innovation development in the new ventures.…”
Section: Coopetitive Dynamics and Knowledge Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the start-ups, finance and advisory services provided by the CBVCs are indispensable for not only its survival (Bertoni et al, 2015;Faria & Barbosa, 2014) but also its internationalization (Humphery-Jenner & Suchard, 2013). An interesting fact shown in prior research is that foreign VC firms outperform the local counterparts in terms of value-adding service (Bringmann et al, 2018). As a result, portfolio financed by CBVCs is more likely to succeed in Initial Public Offering (IPO) (H. Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%